2018
DOI: 10.1101/357624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha-synuclein-induced mitochondrial dysfunction is mediated via a sirtuin 3-dependent pathway

Abstract: 20The sirtuins are highly conserved nicotinamide adenine dinucleotide (NAD + )-dependent en-21 zymes that play a broad role in cellular metabolism and aging. Mitochondrial sirtuin 3 22 (SIRT3) is downregulated in aging and age-associated diseases such as cancer and neuro-23 degeneration and plays a major role in maintaining mitochondrial function and preventing 24 oxidative stress. Mitochondria dysfunction is central to the pathogenesis of Parkinson disease 25 with mutations in mitochondrial-associated protein… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 53 publications
5
29
0
Order By: Relevance
“…Studies have also shown that SIRT3 downregulation in the presence of α-synuclein accumulation is accompanied by increased phosphorylation of AMPK, cAMP-response element-binding protein (CREB), and DRP1, as well as decreased levels of OPA1. These results imply impaired mitochondrial dynamics, further supporting the protective role of SIRT3 in relevant PD pathways (Park et al, 2018).…”
Section: Parkinson’s Diseasesupporting
confidence: 63%
“…Studies have also shown that SIRT3 downregulation in the presence of α-synuclein accumulation is accompanied by increased phosphorylation of AMPK, cAMP-response element-binding protein (CREB), and DRP1, as well as decreased levels of OPA1. These results imply impaired mitochondrial dynamics, further supporting the protective role of SIRT3 in relevant PD pathways (Park et al, 2018).…”
Section: Parkinson’s Diseasesupporting
confidence: 63%
“…Mitochondrial dysfunction leads to the production of reactive oxygen species and can directly interact with variety of specific proteins to be involved in neurodegenerative disorders (Lin & Beal, 2006). For example, in PD aSyn aggregates may induce neurodegeneration by causing a mitochondrial dysfunction and, thereby, the increased production of reactive oxygen species (ROS) (Park et al, 2020; Santos & Outeiro, 2020; Szegő É et al, 2019; Wang et al, 2019). For this reason, we measured intracellular ROS production in differentiated SH-SY5Y cells treated with aggregates formed in the absence or presence of 100 μM doxycycline.…”
Section: Resultsmentioning
confidence: 99%
“…It may also cause mitochondrial dysfunction and enhanced production of ROS, which may, in turn, further modulate aSyn oligomerization and cytotoxicity, leading to a vicious circle. The generation of ROS by aSyn aggregates can affect macromolecules or activate signalling pathways that culminate in central nervous system neurodegeneration (Park et al, 2020; Wang et al, 2019). For this reason, the inhibition of oxidative stress could offer an effective therapeutic approach to mitigate the progression of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Based on in vitro and in vivo studies, α-syn seems to play a central role in the pathological changes through a direct interaction with components of cellular pathways essential for cell homeostasis (Figure 2). Thus, pathological α-syn is able to bind and inhibit lysosomal function (Mazzulli et al, 2016;Flavin et al, 2017), proteasomal activity (Stefanis et al, 2001;Tanaka et al, 2001;Petrucelli et al, 2002;Snyder et al, 2003;Lindersson et al, 2004;Emmanouilidou et al, 2010), to impair axonal transport (Volpicelli-Daley, 2017), and to induce Ca 2+ dyshomeostasis (Danzer et al, 2007;Chen Y. et al, 2015;Angelova et al, 2016) and mitochondrial dysfunction (Di Maio et al, 2016;Ganjam et al, 2019;Wang et al, 2019;Park et al, 2020). Latter promotes the generation of reactive oxygen species (ROS), and therefore oxidative stress, which may lead to mitochondrial damage, the release of cytochrome c to the cytoplasm, and cell death (Hsu et al, 2000;Smith et al, 2005;Parihar et al, 2008;Reeve et al, 2015;Tapias et al, 2017;Ludtmann et al, 2018).…”
Section: α-Syn and Neurodegeneration: α-Synucleionopathiesmentioning
confidence: 99%